2013
DOI: 10.1002/pssa.201300169
|View full text |Cite
|
Sign up to set email alerts
|

Advanced CMOS devices: Challenges and implant solutions

Abstract: In this paper, we first review the trends for advanced CMOS devices in terms of architectures and scalability. The paper highlights the key process challenges for planar MOSFET and FinFET device technologies. We emphasize the need for advanced implant solutions to enable device scaling and performance as well as variability improvement. Especially, we discuss the latest damage engineering solutions as well as materials modification techniques (e.g., contact and strain engineering) to reduce leakage, improve dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…For several years, this niche of application has been almost the only one where germanium was considered as leading material. Recently, the increasingly demanding miniaturization of electronic devices reached the intrinsic limit to the physical nature of silicon and a renewed interest in SiGe and Ge-based MOS-based devices can be perceived, as shown by literature appearing on this topic [1,2]. Ge displays higher mobility of carriers and lower bandgap than silicon, nevertheless has the remarkable disadvantage of a less efficient surface passivation.…”
Section: Introductionmentioning
confidence: 98%
“…For several years, this niche of application has been almost the only one where germanium was considered as leading material. Recently, the increasingly demanding miniaturization of electronic devices reached the intrinsic limit to the physical nature of silicon and a renewed interest in SiGe and Ge-based MOS-based devices can be perceived, as shown by literature appearing on this topic [1,2]. Ge displays higher mobility of carriers and lower bandgap than silicon, nevertheless has the remarkable disadvantage of a less efficient surface passivation.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that a narrow fin which is isolated from large crystal volume; surface proximity and the 3D structure make amorphous silicon recrystallization problematic. If the fin is completely amorphized, only a very small seed for recrystallization, which results in a defective growth, and it degrades the resistivity and drive current of the transistors [118,119]. Therefore, for 3D transistors, it is necessary to reduce the amorphization depth created by implantation as well as the annealing to minimize the fin damage.…”
Section: Damage Controlmentioning
confidence: 99%
“…Alternatively, one can consider the use of cold or cryogenic implantations , resulting in a more uniform damage profile and a thicker a‐Ge layer, with less point defects below the a/c interface in the end‐of‐range region. In the case of 10 keV As + implants at −50 °C this has led to the lowest sheet resistance after activation annealing at 600 °C, compared with RT or 400 °C implantations .…”
Section: Alternative Implantation Annealing and Doping Schemesmentioning
confidence: 99%